Should I trust you? Autistic traits predict reduced appearance‐based trust decisions. (13th November 2018) - Hooper, Jasmine J.; Sutherland, Clare A. M.; Ewing, Louise; Langdon, Robyn; Caruana, Nathan; Connaughton, Emily; Williams, Nikolas; Greenwell‐Barnden, Jayden; Rhodes, Gillian
Abstract : Facial impressions of trustworthiness guide social decisions in the general population, as shown by financial lending in economic Trust Games. As an exception, autistic boys fail to use facial impressions to guide trust decisions, despite forming typical facial trustworthiness impressions (Autism, 19, 2015a, 1002). Here, we tested whether this dissociation between forming and using facial impressions of trustworthiness extends to neurotypical men with high levels of autistic traits. Forty‐six Caucasian men completed a multi‐turn Trust Game, a facial trustworthiness impressions task, the Autism‐Spectrum Quotient, and two Theory of Mind tasks. As hypothesized, participants' levels of autistic traits had no observed effect on the impressions formed, but negatively predicted the use of those impressions in trust decisions. Thus, the dissociation between forming and using facial impressions of trustworthiness extends to the broader autism phenotype. More broadly, our results identify autistic traits as an important source of individual variation in the use of facial impressions to guide behaviour. Interestingly, failure to use these impressions could potentially represent rational behaviour, given their limited validity.